2016
DOI: 10.1534/genetics.115.185314
|View full text |Cite
|
Sign up to set email alerts
|

Novel Innate Immune Genes Regulating the Macrophage Response to Gram Positive Bacteria

Abstract: Host variation in Toll-like receptors and other innate immune signaling molecules alters infection susceptibility. However, only a portion of the variability observed in the innate immune response is accounted for by known genes in these pathways. Thus, the identification of additional genes that regulate the response to Gram positive bacteria is warranted. Bone marrow-derived macrophages (BMMs) from 43 inbred mouse strains were stimulated with lipotechoic acid (LTA), a major component of the Gram positive bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…FBXO17 expression did not modulate IL-10 levels with any stimuli used, and the F-box protein did not significantly alter IL-6 and KC production by MLE cells in response to lipoteichoic acid (LTA) or PamCys3 (data not shown). These results differ from a genome-wide study by Alper et al (35) in which FBXO17 was identified as a possible proinflammatory gene in innate immune responses to LTA. In that study, knockdown of FBXO17 expression in RAW macrophages resulted in a blunted response to LTA stimulation, and its overexpression led to enhanced NF-B promoter activity.…”
Section: Degradation Of Gsk3␤ By Fbxo17 Abrogates Inflammatory Cytokicontrasting
confidence: 99%
“…FBXO17 expression did not modulate IL-10 levels with any stimuli used, and the F-box protein did not significantly alter IL-6 and KC production by MLE cells in response to lipoteichoic acid (LTA) or PamCys3 (data not shown). These results differ from a genome-wide study by Alper et al (35) in which FBXO17 was identified as a possible proinflammatory gene in innate immune responses to LTA. In that study, knockdown of FBXO17 expression in RAW macrophages resulted in a blunted response to LTA stimulation, and its overexpression led to enhanced NF-B promoter activity.…”
Section: Degradation Of Gsk3␤ By Fbxo17 Abrogates Inflammatory Cytokicontrasting
confidence: 99%
“…The enhancement of Th1 immunity by LAB, which is induced by IL-12 production from antigen-presenting cells, was observed in experimental animals ( 25 , 26 , 38 , 39 ). Major components of the bacterial cell wall from Gram-positive bacteria enhanced IL-12 production by DCs or macrophages via TLR2 and/or TLR4 signaling ( 40 , 41 ). However, in addition to those knowledge, we have shown that bacterial RNA is strongly involved in the induction of IL-12 production upon stimulation with LAB.…”
Section: Discussionmentioning
confidence: 99%
“…As long as researchers study about genomic projects, only small portion of the genetic variability observed in the innate immune response is accounted in these pathways. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%